Estimating the Equilibrium Real Exchange Rate : An Application to Finland - Feyzioglu, Tarhan (IMF Working Papers; Working Paper ;, 1997)
An equilibrium exchange rate is here defined as the level that is consistent with simultaneous internal and external balances as specified in Montiel (1996). Exogenous 'fundamental' variables determining these balances are identified. Along the lines of Edwards (1994), a reduced form is estimated with the cointegration technique for Finland for the period 1975-95. The estimation produced a reasonable set of equilibrium exchange rates that appreciate with positive shocks to the terms of trade, world real interest rates, and the productivity differential between Finland and its trading partners.